Sistema de regulación automática de variables ambientales con dispositivos de medición inalámbricos, para galpones avícolas - Ruiz-Barquero, Aníbal (Instituto Tecnológico de Costa Rica, 2008)
In the process of breeding birds such as chicken, the environmental comfort of the bird is the most important part of the process. Environmental variables of temperature and relative humidity should be kept within certain ranges depending on the age of the animal. The whole process of rearing takes place within closed or partially closed structures called “galpones”, barns open and barns in the form of tunnel respectively. It is there within these structures where the environment variables should be regulated. Nowadays the company uses electronic systems mainly from American companies such as Chore-Tronics and Hired-Hand, which handle the on/off of several devices to keep the environmental variables within a specific range. These systems have features that could be dispensable in the process, making them more expensive for some producers. A system that only makes the essential functions in the process, offering a lowest cost choice to produce, was designed in this project. The system has independent units of measurement that work with wireless communication and can extract data records in Flash memories by USB port. The expected result was obtained of a successful way; through field tests was found that the system has a very good communication link and to same time has a proper handling of the actuators.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2008.
Keywords: Temperatura; Humedad relativa; Módulos; Microcontroladores; Sensores; Datos